Jewish life in Belarus : the final decade of the Stalin regime, 1944-53 - Smilovit͡skiĭ, Leonid, 1955- (Publications of the Goldstein-Goren Diaspora Research Center, 2014)
Jewish life in Belarus after World War II was an inaccessible subject - officially regarded as being completely non-existent - and in the ideological atmosphere of the time research into the subject was impossible. Jewish community life had been wiped out by the Nazis, and its unreasonable attempt to come back to life was given short shrift by the communists. For more than half a century the truth about Jewish life during this period was sealed in archives to which researchers had no access. The Jews of Belarus preferred to keep silent rather than expose themselves to the spleen of the authorities. Although the fate of Belarusian Jews before and during the war has lately been amply studied, this book is one of the first attempts to study Jewish life in Belarus during the last decade of Stalin's rule. In addition to archival materials, the present research is based on data collected from a questionnaire submitted to Jews who had been residents of Belarus and are now citizens of Israel, as well as information from periodicals, collections of documents, statistical reports and monographs.